PENGARUH PAJAK, EXCHANGE RATE, TUNNELING INCENTIVE, DAN LEVERAGE TERHADAP TRANSFER PRICING (Studi Empiris Pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Bela Pratiwi (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of tax, exchange rate, tunneling incentive, and leverage to transfer pricing. Dependent variable in this study is transfer pricing which is proxied with the value from a related party transaction (RPT) of sale. The independent variables in this study are tax, exchange rate, tunneling incentive, and leverage. This study took the secondary data in financial statements or annual reports that have been published by companies in Indonesia Stock Exchange. The population in this study are all the manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. This study took manufacturing companies listed on the Indonesia Stock Exchange as sample, especially the various industry sectors from years 2012-2016. Sampling technique used in this study was purposive sampling method. The total number of sample in this study is 35 firm years from seven companies. The analytical method used was logistic regression analysis using SPSS program version 16. The results of the analysis in this study indicate that tax, exchange rate, and tunneling incentive have no significant effect on transfer pricing, whereas leverage has a significant positive effect on transfer pricing. Keywords: Transfer Pricing, Tax, Exchange Rate, Incentive Tunneling, Leverage.